Pengelolaan Bantuan Dana Operasional Sekolah dalam Meningkatkan Mutu Pendidikan di SMK Musda Perbauangan - Novija Julinar (UMSU, 2023)
This study aims to describe the management of school operational assistance funds in improving the quality of education at SMK Musda Perbaungan, Serdang Bedagai Regency 2022/2023 academic year. This research is qualitative research with a descriptive approach. In this study, data sources were obtained from the school principal, school committee, treasurer, head of administration, and teacher. The data collection techniques used in this study are observation, interviews, and documentation study. The data validity test was carried out by triangulation of techniques and sources. The results of the study show that the management of school operational assistance funds in improving the quality of education at SMK Musda Perbaungan applies the principles of school-based management, starting from budget planning referring to school quality report cards. The use of the school operational assistance fund budget is based on the priority scale from the mapping of needs that have been submitted by teachers and school residents which are allocated in accordance with national education standards. Supervision in the use of the budget is carried out by school internal and external parties. Accountability reports are made in accordance with the format contained in the applicable technical guidelines. There is an increase in the quality of education at SMK Musda Perbaungan due to the management of budget funds that are used effectively and efficiently.